Aligning Human Resource Information Systems (HRIS) with the Imperatives of Society 5.0: A Strategic Framework for Digital Talent Management in the Indonesian Banking Sector - Lia Ovi Arini; Dessy Nur Ardillah; Syahrial Shaddiq (Jurnal Riset Multidisiplin Edukasi, 2025)
The rapid acceleration of digital transformation, spurred by the global pandemic and new economic demands, has placed the Indonesian banking sector at a critical juncture. Amidst this disruption, the Society 5.0 paradigm has emerged as a human-centric vision, proposing a deep integration of technology and society to enhance the quality of life. However, the success of this transformation hinges on its most vital asset: digital talent. A significant gap currently exists between the strategic capabilities of modern Human Resource Information Systems (HRIS) and the imperative to effectively manage digital talent in alignment with Society 5.0. This research aims to bridge this gap by developing a comprehensive conceptual framework, titled "Strategic Talent Alignment for a Resilient Human-centric Information System" (STAR-HRIS). Employing a systematic literature review, this study synthesizes findings from diverse sources, including academic journals, industry reports, and policy documents from regulatory bodies such as the Indonesian Financial Services Authority (OJK). The results present the STAR-HRIS framework, which is composed of three layers: (1) The Foundation of Governance & Digital Infrastructure, encompassing the technology stack, data governance, and digital ethics; (2) The Pillars of Intelligent Talent Management, which include intelligent talent acquisition, adaptive talent development, and dynamic, AI-powered engagement and retention; and (3) The Organizational Enablers, which highlight the crucial roles of digital leadership, an innovative culture, and change management. The discussion interprets how the STAR-HRIS framework can serve as a roadmap for banking leaders and HR practitioners in Indonesia to evolve their HRIS from an administrative system into a dynamic talent ecosystem. This framework not only offers a practical solution to the digital talent gap but also emphasizes the importance of ethical considerations in AI implementation, consistent with the human-centric philosophy of Society 5.0. This research contributes an actionable strategic model for aligning technology, people, and strategy to navigate the future of the banking sector.